Bounds between animals and humans in The Grapes of Wrath by John E. Steinbeck, Vidas Secas by Graciliano Ramos and Porteira Fechada by Cyro Martins - Devincenzi, Isabel Speggiorin (BELT - Brazilian English Language Teaching Journal, 2014)
The relation between animals and human beings was analyzed in three novels – Vidas Secas (1938) by Graciliano Ramos, The Grapes of Wrath (1939) by John E. Steinbeck and Porteira Fechada (1944) by Cyro Martins – as possible reflections of social and economic transformations in the countryside during the decades of 30’s and 40’s. The Grapes of Wrath portraits the period of the Great Depression in the Unite States, and Vidas Secas and Porteira Fechada, the period of Estado Novo (1937-1945) in Brazil. First, it was analyzed the animal characterization of the novels’ characters; secondly, how animals were present in the work order in the countryside; thirdly, the relation between the novels’ characters and animals. This study may indicate that the relationship between the characters and the animals in the selected novels are marked by rupture, as some groups of the Brazilian and the American society were experiencing a rupture of values at that time.